On the concept of 'village' in Northeastern Afghanistan: Explorations from Kunduz Province - Katja Mielke (University of Bonn, Center for Development Research (ZEF), 2007)
This paper discusses contesting notions of 'the local' in Northeastern Afghanistan's Kunduz province. Empirical evidence suggests that a high fluidity and pluralistic nature of the notion of 'village' exists at the local level within the boundaries of three irrigation systems. Taking into account the settlement history of the oasis landscape in Kunduz, the paper demonstrates the local government's limited capacity to survey and register land allocations and the establishment of rural settlements. The current implementation of the National Solidarity Program can be read as an attempt to correct the government's so-perceived governance deficit with regard to the rural countryside. The establishment and official registration of Community Development Councils potentially provides the foundation of a future fourth administrative tier resembling CDC-communities. Critical thoughts of how these newly established concepts of community match local population's notion of community and identity conclude the paper.
Keywords: 330; concepts of local; community; village; National Solidarity Program; Afghanistan; Kunduz